It follows [videorecording (DVD)] - Monroe, Maika; Gilchrist, Keir, 1992-; Zovatto G., Daniel (Anchor Bay Entertainment, 2015)
For nineteen-year-old Jay, the fall should be about school, boys and weekends at the lake. Yet, after a seemingly innocent sexual encounter she suddenly finds herself plagued by nightmarish visions; she can't shake the sensation that someone, or something, is following her. As the threat closes in, Jay and her friends must somehow escape the horrors that are only a few steps behind.